Biostimulants for the regulation of reactive oxygen species metabolism in plants under abiotic stress - Hasanuzzaman, Mirza; Parvin, Khursheda; Bardhan, Kirti; Nahar, Kamrun; Anee, Taufika Islam; Masud, Abdul Awal Chowdhury; Fotopoulos, Vasileios (My University, 2021)
Global food security for a growing population with finite resources is often challenged by multiple, simultaneously occurring on-farm abiotic stresses (i.e., drought, salinity, low and high temperature, waterlogging, metal toxicity, etc.) due to climatic uncertainties and variability. Breed-ing for multiple stress tolerance is a long-term solution, though developing multiple-stress-tolerant crop varieties is still a challenge. Generation of reactive oxygen species in plant cells is a common response under diverse multiple abiotic stresses which play dual role of signaling molecules or damaging agents depending on concentration. Thus, a delicate balance of reactive oxygen species generation under stress may improve crop health, which depends on the natural antioxidant defense system of the plants. Biostimulants represent a promising type of environment-friendly for-mulation based on natural products that are frequently used exogenously to enhance abiotic stress tolerance. In this review, we illustrate the potential of diverse biostimulants on the activity of the antioxidant defense system of major crop plants under stress conditions and their other roles in the management of abiotic stresses. Biostimulants have the potential to overcome oxidative stress, though their wider applicability is tightly regulated by dose, crop growth stage, variety and type of biostimulants. However, these limitations can be overcome with the understanding of biostimu-lants’ interaction with ROS signaling and the antioxidant defense system of the plants.
Keywords: Antioxidant defense; Organic amendments; Phenolic compounds; Phytohormones; Trace elements; Stress tolerance; Sustainable agriculture